The New Yorker Theater and other scenes from a life at the movies - Talbot, Toby (Columbia University Press, 2009)
The nation didn't know it, but 1960 would change American film forever, and the revolution would occur nowhere near a Hollywood set. With the opening of the New Yorker Theater, a cinema located at the heart of Manhattan's Upper West Side, cutting-edge films from around the world were screened for an eager audience, including the city's most influential producers, directors, critics, and writers. Woody Allen, Martin Scorsese, Susan Sontag, Andrew Sarris, and Pauline Kael, among many others, would make the New Yorker their home, trusting in the owners' impeccable taste and incorporating much of what they viewed into their work. In this irresistible memoir, Toby Talbot, co-owner and proud "matron" of the New Yorker Theater, reveals the story behind Manhattan's wild and wonderful affair with art-house film. With her husband Dan, Talbot showcased a range of eclectic films, introducing French New Wave and New German cinema, along with other groundbreaking genres and styles. As Vietnam protests and the struggle for civil rights raged outside, the Talbots also took the lead in distributing political films, such as Bernard Bertolucci's Before the Revolution, and documentaries, such as Shoah and Point of Order. Talbot enhances her stories with selections from the New Yorker's essential archives, including program notes by Jack Kerouac, Jules Feiffer, Peter Bogdanovich, Jonas Mekas, Jack Gelber, and Harold Humes. These artifacts testify to the deeply engaged and collaborative spirit behind each showing, and they illuminate the myriad--and often entertaining--aspects of theater operation. All in all, Talbot's tales capture the highs and lows of a thrilling era in filmmaking.--